Transformation of Education for the Information Professionals: A Special Reference to the University of Hacettepe - İrfan Çakın (Türk Kütüphaneciliği)
Institutions responsible for educating Information professionals inevitably res- poııd to the challenges of multi-dimensional changes in the society. This artic- le not only underlines the problems of the Department of Lıbrary Science at Hacettepe University in relation to its existing undergraduate programmes, but also aims to introduce and discuss a very recently developed curriculum that is hoped to meet the challenges of the professional market at large.